Ten Years of Islamic Accounting: Bibliometrik Analysis - Julia Noermawati Eka Satyarini; Rofiul Wahyudi; Aqidah Asri Suwarsi; Amelia Manggala Putri (International Journal of Economics, Business and Innovation Research, 2024)
This study examines the trend of Islamic accounting publications using bibliometric analysis. The authors used co-citation and co-word analysis to examine 449 Islamic education and finance studies from Scopus. In the co-citation analysis, seven clusters of Islamic accounting themes were identified. After that, co-word analysis is used to understand each research theme and to uncover potential future research directions. The results showed that the average publication of articles was 18.3 per year over the last ten years. Malaysia, the United Kingdom, Tunisia, the UAE, and Indonesia are leading countries in Islamic accounting as centers of significant research activities. Furthermore, the Journal of Islamic Accounting and Business Research and the International Journal of Islamic and Middle Eastern Finance and Management are two journals that are the center of attention of researchers in publishing Islamic accounting topics. The field of research is related to Islamic accounting, which includes financial systems, capital markets, financial services, finance, financial performance, and investment. One of the new keys of COVID-19' is related to Islamic accounting. This new keyword in Islamic accounting research indicates that the research seeks to identify, analyze, and provide solutions to the impact of the pandemic on the Islamic accounting context.